(untitled) (Journal of Geography and Environmental Management, 2017)
The problem of quality of drinking water affects many aspects of society: social, political, geographical, medical, etc. Drinking water varnasi factor of human health. How important is water to humans is evidenced by the fact that its content in various organs is 70-90%.Therefore, the study of the quality of the water consumed by residents of the city of Almaty is relevant. Almaty city is supplied with water from several sources – the rivers Big and Small Almaty (1/3, after cleaning the filter) and groundwater of the territory of Almaty and Talgar. Every day the city receives thousands 550 cubic metres of water. The article presents daily order quality control pitivi consumption of water by the population of the city and conducted studies of the water used by the students of the hostel № 4 of the Kazakh national university. In the process of monitoring drinking water applied physico-chemical and «inductive plasma atomic emission spectrometer (iCAP 6000)» methods. The results of the study determined the composition of water quality of Almaty.